Structural, morphological and thermal properties of nano Filler produced from date palm-based micro (fibers phoenix dactylifera L.) - Alothman, Othman Y.; Shaikh, Hamid M.; Alshammari, Basheer A.; Mohammad Jawaid, . (Springer, 2021)
In this century, the development of nano-sized filler from biomass material has become the main focus of industries in achieving their final green composite product for a wide range of applications. From a commercial and environmental point of view, fragmentation and downsizing of waste lignocellulosic fibers without chemical treatments into small size particles is a viable option. In this study, an attempt was made to produce nano-sized lignocellulosic fillers from date palm micro fibers via mechanical ball milling process at intense 99 cycles run (equivalent to 25 h). The resultant nanofillers as well as the microfibers were characterized in details by various analytical techniques, including transmission electron microscopy (TEM), scanning electron microscopy (SEM), particle size analysis (PSA), Energy Dispersive X-Ray (EDX), X-ray diffraction (XRD), thermogravimetric analysis (TGA), and differential scanning calorimetry (DSC) to assess their structure—property relationship. From microscopy examination, the nanofillers showed a heterogeneous mix of irregular shaped particles, and while having a size ranging of 30–110 nm in width and 1–10 mm length dimensions. Also, the crystallography analysis revealed the crystallinity had mildly declined from microfibers (71.8%) to nanofiller (68.9%) due to amorphization effect. As for thermal analysis, the nanofillers exhibited high heat resistance at 260.8 °C decomposition temperature. Furthermore, the nanofillers also had stable thermo-changing behavior by presenting low heat enthalpy change (40.15 J/g) in its endothermic reaction for breaking organic bonds. The thermal results suggest its suitability for composite fabrication process at high temperature. Thus, the produced nanofillers can be used as a low cost reinforcing agent in the future for versatile polymer-based composite systems.